Design thermohygrometer based on internet of things in clinical laboratory - I Made Agus Mahardiananta; Putu Vierda Lya Suandari; I Gusti Agung Ngurah Devasya Putra Pratama (Indonesian Journal of Electrical Engineering and Computer Science, 2023)
Clinical laboratory units must meet safety requirements such as temperature stability and room humidity because the materials and substances used are sensitive to changes in temperature and environmental conditions, so it is important to carry out routine monitoring. The purpose of this research is to design an internet of things (IoT)-based thermohygrometer that can make it easier for users to monitor temperature and humidity even though the user is outside the laboratory. This tool can also store the results of temperature and humidity measurements making it easier for the user to monitor changes in temperature and humidity that occur. The method used is descriptive exploratory with a prototype system, namely the system development process, users and the required data and results obtained through a tool that has been designed. The results of research conducted using an IoT-based thermohygrometer prototype after statistical testing, there was no significant difference between the reference thermohygrometer and the IoT-based thermohygrometer prototype and the readings from the thinkspeak web. For temperature and humidity measurements that have been carried out at the X clinical laboratory in Denpasar, it still does not meet the standards.